IDENTIFIKASI KESULITAN GURU MATEMATIKA DALAM PEMBELAJARAN DARING PADA SAAT COVID-19 - Anzora, Anzora; Musriandi, Riki; Romita, Romita; Aryani, Irma; Hasanah, Hasanah (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to identify teacher difficulties in the online learning process on 8 indicators, namely internet quota indicators, limited mastery of information technology, facilities and infrastructure, unstable networks, learning applications, learning management, learning assessment, and task execution. Online learning is an educational innovation that involves elements of information technology in learning. This research is a qualitative research using descriptive method. Respondents in this study were 12 mathematics teachers at SMA Banda Aceh. Data collection techniques in the form of questionnaires and analyzed using qualitative descriptive data techniques. The results showed that there were 16 indicators that became difficulties for mathematics teachers in the online learning process, namely, using various learning media (41.7%), many other economic needs that must be met (41.7%), not accustomed to using online learning applications. (75%), do not understand about online learning (50%), online learning facilities used by students are owned by their parents (50%), some students complain that they cannot send assignments because they are constrained by the internet network (50%), there is no internet signal ( 75%), bad weather conditions cause internet network to be disrupted (58.3%), difficult to see the achievement of basic competencies mastered by students (50%), difficulty in attitude assessment (50%), difficulty monitoring student learning progress (50%) , lack of student understanding of learning materials (58.3%), learning tends to be more task-oriented (58.3%), students' lack of interest in online learning (91.7%), the difficulty of economic needs students so that they have to work (75%), and students are bored and bored studying online (50%). This shows that there are still things that are difficult for math teachers in online learning during covid-19.Keywords : Online Learning, Difficulty, Mathematics